1996
DOI: 10.1038/bjc.1996.155
|View full text |Cite
|
Sign up to set email alerts
|

Ranitidine and cimetidine differ in their in vitro and in vivo effects on human colonic cancer growth

Abstract: Summary Histamine has recently been shown to be a growth factor for some gastric and colorectal cancer cells. Previous studies have shown that cimetidine blocks in vitro and in vivo histamine-stimulated growth and cAMP release from the human colonic cancer cell line, C170. In this study, ranitidine, another H2 receptor antagonist, did not affect either basal or histamine-stimulated in vitro proliferation of C170, and failed to prevent cAMP release in vitro. Ranitidine did not inhibit in vivo growth of C170 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 18 publications
(8 reference statements)
2
41
0
Order By: Relevance
“…Together, these findings suggest that the anti-tumor effects of cimetidine require a stimulating effect of histamine toward tumor cell growth, which is mediated via histamine H 2 receptors on tumor cells. However, other H 2 receptor antagonists such as ranitidine and famotidine did not exert anti-tumor effects in previous in vitro and in vivo studies, despite their stronger acid-inhibiting activity as compared to cimetidine (29)(30)(31). In a cell proliferating assay previously performed, famotidine did not have an effect on either histamine-stimulated or basal proliferation of HCC cell lines (data not shown), which shows that the mechanisms of the inhibitory effects of cimetidine on tumor cell proliferation are not limited to blocking the H 2 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these findings suggest that the anti-tumor effects of cimetidine require a stimulating effect of histamine toward tumor cell growth, which is mediated via histamine H 2 receptors on tumor cells. However, other H 2 receptor antagonists such as ranitidine and famotidine did not exert anti-tumor effects in previous in vitro and in vivo studies, despite their stronger acid-inhibiting activity as compared to cimetidine (29)(30)(31). In a cell proliferating assay previously performed, famotidine did not have an effect on either histamine-stimulated or basal proliferation of HCC cell lines (data not shown), which shows that the mechanisms of the inhibitory effects of cimetidine on tumor cell proliferation are not limited to blocking the H 2 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been observed that histamine was a growth factor for certain cancers and could, by itself, stimulate tumor cell proliferation [18][19][20] . As one of the many important chemo-mediators involved in immune responses, histamine had inhibitory effects on immune response [35][36][37][38] via its H 2 receptors [39] .…”
Section: Discussionmentioning
confidence: 99%
“…Administration of CIM has been found to preserve, to some degree, the patients' perioperative immunity [5,6] , to improve the survival of patients with colorectal cancer, melanoma, and renal cell cancer [7][8][9][10][11][12][13][14][15] . Although it is not clear whether this effect of CIM on cancer is direct or indirect, it has been proposed that CIM may act by enhancing the host immune response to tumor cells [16,17] or by blocking the cell growth-promoting activity of histamine in cancer cell lines [14,[16][17][18][19][20] . In this study, we used CIM in the perioperative period as an adjuvant immunomodulatory agent, and studied its effects on peripheral blood lymphocytes, NK cells and TIL in a randomized controlled clinical trial in patients with GI cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Because famotidine behaves as a specific H 2 receptor antagonist with a molar potency four to eight times greater than that of cimetidine (Peden et al, 1982;Feldman and Burton, 1990), it is Molecular and Cellular Pathology (Morris and Adams, 1995;Lawson et al, 1996). Kobayashi et al (2000) showed that cimetidine can block the adhesion of colorectal cancer cells to the endothelial cells, suppressing the metastases of cancer cells.…”
Section: Molecular and Cellular Pathologymentioning
confidence: 99%